2002
DOI: 10.1354/vp.39-5-557
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Tumors of the Gastrointestinal Tract in 39 Dogs

Abstract: Abstract. Mast cell tumors (MCTs) of gastrointestinal origin that had been surgically removed from 39 dogs were examined to evaluate their pathologic features. Miniature breeds, especially Maltese, were most frequently affected. The average age of affected dogs was 9.7 Ϯ 2.6 years. No sex difference was apparent. The most frequently affected sites were in the upper digestive tract, and the prognosis was very poor. Grossly, the gastrointestinal wall was prominently thickened, and the lumen of the affected gut w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
17

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 15 publications
2
48
1
17
Order By: Relevance
“…In France, relatively many young boxers were found to suffer from MCTs of low grade malignancy (9). Purebred male dogs of miniature breeds appear to have a relative high prevalence of intestinal MCTs (85,106). All breeds are susceptible however and both sexes are equally affected (9).…”
Section: Canine Mast Cell Tumours Epidemiology and Aetiologymentioning
confidence: 99%
“…In France, relatively many young boxers were found to suffer from MCTs of low grade malignancy (9). Purebred male dogs of miniature breeds appear to have a relative high prevalence of intestinal MCTs (85,106). All breeds are susceptible however and both sexes are equally affected (9).…”
Section: Canine Mast Cell Tumours Epidemiology and Aetiologymentioning
confidence: 99%
“…After blocking with 2.5% heat-inactivated horse serum, the preparations were incubated overnight with mouse antihuman tryptase monoclonal antibody (clone AAI; Serotec, Oxford, U.K.) or mouse IgG 1 isotype control (Rockland, Gilbertsville, PA, U.S.A.) diluted with 1.5% heat-inactivated horse serum in PBS at 4C. The anti-human tryptase monoclonal antibody has previously been shown to be cross-reactive with canine tryptase by immunohistochemistry [31]. The preparations were incubated with biotinylated panspecific universal secondary antibody and then a biotinstreptavidin peroxidase complex method was carried out according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…(Neiger, 2008), Gnathostoma spp. (McCarthy et al, 2000), Heterobilharzia americana (Rodriguez et al, 2014) and mastocytoma along with infiltration of eosinophils (Ozaki et al, 2002), lesions are rarely observed in Toxocara canis infestation (Chira et al, 2005). Focal type chronic hypertrophy occurs as a result of chronic administration of Aspirin.…”
Section: Classification Of Gastritismentioning
confidence: 99%
“…Animals with mastocytosis may have numerous all over gastric ulcers (Stanton and Bright, 1989;Ozaki et al, 2002). The mast cell tumor produces and releases histamine, which binds to H2 receptors on gastric parietal cells, gives a powerful stimulant to acid secretion.…”
Section: Etiopathogenesis Of Gastritis and Peptic Ulcer Diseasesmentioning
confidence: 99%